2013
DOI: 10.1159/000350097
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Inhibits Abnormal Proliferation of Lymphocytes via AKT/GSK3� Signal Pathway in Systemic Lupus Erythematosus Patients

Abstract: Background/Aim: The abnormal activation of the AKT/GSK3β signal pathway in lymphocytes from systemic lupus erythematosus (SLE) patients plays an important role in the pathogenesis of the disease. Recently Hydrogen sulfide (H2S) has been recognized as a crucial gaseous signaling molecule, involved in regulation of cell proliferation. However, the role of H2S in regulating the abnormal activation of lymphocytes from SLE patients has not been established. This study was conducted to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 22 publications
(34 reference statements)
2
29
0
Order By: Relevance
“…H 2 S decreased the expression of the P47 NADPH oxidase subunit, which is related to oxidative stress stimulation via the NF-κB pathway. Some studies demonstrated that treatment with exogenous H 2 S suppresses the expression of pro-fibrotic genes fibronectin and galectin-3 mRNA levels, and the expression of fibrotic marker CTGF in AngII-stimulated cardiac fibroblasts [14,41,42]. Our previous studies have shown that NaHS (a H 2 S donor) was potent at inhibiting NOX4 expression and activity under oxidative stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 S decreased the expression of the P47 NADPH oxidase subunit, which is related to oxidative stress stimulation via the NF-κB pathway. Some studies demonstrated that treatment with exogenous H 2 S suppresses the expression of pro-fibrotic genes fibronectin and galectin-3 mRNA levels, and the expression of fibrotic marker CTGF in AngII-stimulated cardiac fibroblasts [14,41,42]. Our previous studies have shown that NaHS (a H 2 S donor) was potent at inhibiting NOX4 expression and activity under oxidative stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, H 2 S, a gasotransmitter, has attracted wide attention because of its protective effect of brain, liver, kidney, heart, lung and other organs [20][21][22][23][24]. Many studies have demonstrated the cytoprotective effects of H 2 S in myocardial IR injury [25,26].…”
Section: Lc3-ii Protein Atg5 and Beclin1 Mrna Were Down-regulated Bymentioning
confidence: 99%
“…Recently in a rat model, H 2 S was reported to protect cardiomyoblasts against oxidative challenge through the inhibition of L-type calcium channels [6]. More importantly in systemic lupus erythematosus patients, H 2 S was found to inhibit the abnormal activation of lymphocytes through the AKT/GSK3β signal pathway [7]. Moreover, an N-mercapto-based H 2 S donor was recently found to protect human skin keratinocytes against methylglyoxalinduced injury and behavior dysfunction [8].…”
Section: Introductionmentioning
confidence: 99%